2021
DOI: 10.5455/javar.2021.h481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular optimization, docking, and dynamic simulation profiling of selective aromatic phytochemical ligands in blocking the SARS-CoV-2 S protein attachment to ACE2 receptor: an in silico approach of targeted drug designing

Abstract: Objectives: The comprehensive in silico study aims to figure out the most effective aromatic phytochemical ligands among a number from a library, considering their pharmacokinetic efficacies in blocking “angiotensin-converting enzyme 2 (ACE2) receptor–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S protein” complex formation as part of a target-specific drug designing. Materials and Methods: A library of 57 aromatic pharmacophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Molecular docking is the process that estimates how two or more molecules bind together with the best structural confirmation and the lowest binding energy. The more significant and efficient drug candidates were selected based on the scoring value of molecular docking using the PyRx virtual screening tool [Version: 0.8] [ 44 , 45 ]. The docking operation for the five phytochemicals and control molecules with receptor SYK kinase found that the docking score of the control was −6.5 Kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking is the process that estimates how two or more molecules bind together with the best structural confirmation and the lowest binding energy. The more significant and efficient drug candidates were selected based on the scoring value of molecular docking using the PyRx virtual screening tool [Version: 0.8] [ 44 , 45 ]. The docking operation for the five phytochemicals and control molecules with receptor SYK kinase found that the docking score of the control was −6.5 Kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Unnecessary things were eliminated, such as the water molecules, metal ions, ligands, heteroatoms, and unwanted side chains. Indispensable hydrogen bonds were also added to the macromolecules for more precise docking, and the total operation was conducted by the “UCSF Chimera package tool (Version-1.14)”, here must followed the “Gasteiger’s method” [ 44 ]. The prepared protein structures were saved in PDB format and conserved for further analysis [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the initial visualization and qualitative receptor–ligand interactions analysis, Discovery Studio Visualizer (version 3.0) and PyMOL (version 2.4.1) were used sequentially, and the output files were saved as PDB files. Afterward, the quantitative hydrophobic interactions and the number of hydrogen bond formations between each of the protein–ligand complexes were analyzed using LigPlot+ (version 2.2) [ 32 ] before conducting the molecular dynamic simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The biostatistical analysis and computational algorithms were performed using computational 'R Programming Scripts' (version R-4.0.2, for Linux) [39,40] and 'GraphPad Prism' (version 8.1.2, for Mac OS) [41,42,43] premium software packages.…”
Section: Software Tools For Data Analysis and Validationmentioning
confidence: 99%